Niche Modulation of IGF-1R Signaling: Its Role in Stem Cell Pluripotency, Cancer Reprogramming, and Therapeutic Applications - Chen, Pei-Chin; Kuo, Yung-Che; Chuong, Cheng-Ming; Huang, Yen-Hua (Frontiers in Cell and Developmental Biology, 2021)
Stem cells work with their niches harmoniously during development. This concept has been extended to cancer pathology for cancer stem cells (CSCs) or cancer reprogramming. IGF-1R, a classical survival signaling, has been shown to regulate stem cell pluripotency, CSCs, or cancer reprogramming. The mechanism underlying such cell fate determination is unclear. We propose the determination is due to different niches in embryo development and tumor malignancy which modulate the consequences of IGF-1R signaling. Here we highlight the modulations of these niche parameters (hypoxia, inflammation, extracellular matrix), and the targeted stem cells (embryonic stem cells, germline stem cells, and mesenchymal stem cells) and CSCs, with relevance to cancer reprogramming. We organize known interaction between IGF-1R signaling and distinct niches in the double-sided cell fate with emerging trends highlighted. Based on these new insights, we propose that, through targeting IGF-1R signaling modulation, stem cell therapy and cancer stemness treatment can be further explored.